2014
DOI: 10.11604/pamj.2014.19.177.4307
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extensively drug-resistant gram negative bacilli in surgical intensive care in Egypt

Abstract: IntroductionThe prevalence of extensively drug resistant gram negative bacilli (XDR-GNB) is rapidly progressing; however in Egypt data are sparse. We conducted the present study to quantify the incidence, risk factors and outcome of patients harboring XDR-GNB.MethodsA one year prospective study was done by collecting all the bacteriological reports for cultures sent from the surgical intensive care unit, Cairo university teaching hospital. XDR-GNB were defined as any gram negative bacilli resistant to three or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
4
18
2
Order By: Relevance
“…More MDR and XDR strains in E. coli than K. pneumoniae in our study could be due to the fact that the number of E. coli strains isolated were more than K. pneumoniae. In regard to XDR and PDR, the current study is supported by the findings of previous studies [30, 31] however our finding strongly disagree with a study conducted by Ahmed Hasanin et al [32] in the prevalence of XDR strains of FGNB. In this study lower XDR E. coli (18%) and K. pneumonia (11%) were reported as compared to the previous study where higher XDR K. pneumoniae (52%), and E. coli (47%) were reported [32].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…More MDR and XDR strains in E. coli than K. pneumoniae in our study could be due to the fact that the number of E. coli strains isolated were more than K. pneumoniae. In regard to XDR and PDR, the current study is supported by the findings of previous studies [30, 31] however our finding strongly disagree with a study conducted by Ahmed Hasanin et al [32] in the prevalence of XDR strains of FGNB. In this study lower XDR E. coli (18%) and K. pneumonia (11%) were reported as compared to the previous study where higher XDR K. pneumoniae (52%), and E. coli (47%) were reported [32].…”
Section: Discussionsupporting
confidence: 54%
“…In regard to XDR and PDR, the current study is supported by the findings of previous studies [30, 31] however our finding strongly disagree with a study conducted by Ahmed Hasanin et al [32] in the prevalence of XDR strains of FGNB. In this study lower XDR E. coli (18%) and K. pneumonia (11%) were reported as compared to the previous study where higher XDR K. pneumoniae (52%), and E. coli (47%) were reported [32]. The reason for the difference in the prevalence of XDR might be due to the definition used to classify isolates into XDR and the location of the patient from (inpatient or outpatient) from where the specimen is obtained.…”
Section: Discussionsupporting
confidence: 54%
“…According to a study conducted in the surgical ICU of the same hospital, susceptibility to IMI was 88.7% versus 73% in our study. 1 The decreasing IMI susceptibility raised our attention to understand the different mechanisms of IMI resistance in our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 62% of rectal swabs were positive for CRE. In another study Hasanin et al, (2014) conducted a survey in Egypt for one-year duration, a total of 152 samples (65%) out of 234 gram negative bacilli samples developed extensively drug resistant infection. This high rate of CRE in Egypt is attributed to over the counter antibiotic abuse, noncompliance with antimicrobial stewardships and infection control measures in hospitals.…”
Section: Cdc Laboratory Protocol For Detection Of Crementioning
confidence: 99%